Pengembangan Pembelajaran Pendidikan Kewarganegaraan Di Sekolah Dasar - Titin Sunaryati; Trias Wibiwirutami; Habibah Habibah; Khopipah Khopipah; Alya Rasikhah Zahra Rossi (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
Civic development in primary schools is a process that improves the quality of learning and creates an inspiring environment for students to instill civic values. The purpose of this study is to examine the development of civics in primary schools. The research method is literature review. The results of this study indicate that the development of Civics learning in primary schools is a process to improve the quality of learning and create a conducive environment for students to promote civic values. With good Civics Education, students are expected to understand their rights and obligations as citizens, respect differences, behave democratically, and participate in building a better society.